Molecular Mechanisms of the Whole DNA Repair System: A Comparison of Bacterial and Eukaryotic Systems - Morita, Rihito; Nakane, Shuhei; Shimada, Atsuhiro; Inoue, Masao; Iino, Hitoshi; Wakamatsu, Taisuke; Fukui, Kenji; Nakagawa, Noriko; Masui, Ryoji; Kuramitsu, Seiki (Journal of Nucleic Acids, 2010)
DNA is subjected to many endogenous and exogenous damages. All organisms have developed a complex network of DNA repair mechanisms. A variety of different DNA repair pathways have been reported: direct reversal, base excision repair, nucleotide excision repair, mismatch repair, and recombination repair pathways. Recent studies of the fundamental mechanisms for DNA repair processes have revealed a complexity beyond that initially expected, with inter- and intrapathway complementation as well as functional interactions between proteins involved in repair pathways. In this paper we give a broad overview of the whole DNA repair system and focus on the molecular basis of the repair machineries, particularly in Thermus thermophilus HB8.